The collaborative lawyer in Conflict Resolution Methods: a new paradigm guaranteeing human rights in Mexican alternative justice - Aceves Fuentes, Tahalia Esmeralda; Flores Montes, Jazmín Araceli; Cárdenas Voges, Luis Enrique (DIXI, 2026)
This article addresses the current flexibility of the Mexican alternative justice system, also known as MSC, as a new way of guaranteeing the human right of access to justice. The objective is to analyze the concept of collaborative negotiation and the legal scope of the collaborative lawyer as a guarantor of human rights, incorporated in 2024 into the General Law on Alternative Dispute Resolution Mechanisms. To this end, the methodology used was the deductive method, starting from the general to the specific, with a qualitative approach, through documentary analysis of doctrine, collaborative and hermeneutic law, and the application of a survey. This made it possible to identify that collaborative lawyers can support the parties in resolving their conflicts equitably and peacefully through dialogue. However, it is not clear when specifying their powers, limits, and scope within a negotiation. In conclusion, it was identified that lawyers, by acting as advisors and participating together with the parties to achieve solutions that benefit them, contribute to social peace with more just societies in peaceful environments.